PWE-009 Per oral cholangioscopy: systematic evaluation in clinical practice. (23rd September 2015) - Dwyer, L; Polavarapu, N; Hood, S; Sheard, J; Sturgess, R
Abstract : Introduction: A new technological approach to per oral cholangioscopy (POC) has led to a re-examination of this technique for diagnosis and therapy of hepatobiliary disease. We present a single centre experience from a tertiary regional hepatobiliary unit. Methods: Prospective analysis of indications and technical success including direct visualisation, tissue acquirement and analysis and therapeutic success. Analysis of contribution of POC to clinical decision making. Result: Since June 08 to date 36 ERCPs have been undertaken with POC. The indications were indeterminate strictures 28/36 (78%), filling defect 4/36 (11%), POC directed electro-hydraulic lithotripsy (EHL) 4/36 (11%). In one case the bile duct could not be intubated with the cholangioscope. Good views were obtained in 34 of 36 cases (94%). Biopsies were attempted in 16 patients, all of whom had focal mucosal change. Biopsy was not attempted if the mucosa appeared completely normal. In 15 of the 16 cases biopsy was successful in obtaining useful tissue for assessment. 12/15 biopsies were judged to be accurate on basis of either a positive diagnosis of malignancy or a non-malignant result in patients who subsequently had a benign clinical course. Three of the four cases of filling defect were shown to be stones and one a carcinoma. EHL lead to complete stone clearance in three of four cases. The addition of POC appeared to critically influence clinical decision making in 21 of 32 cases (65%). There no significant complications related to the POC procedure that could be identified. Conclusion: POC is currently being re-evaluated in the management of complex hepatobiliary disease. It appears to be safe and add significantly to the information used to manage patients with indeterminate strictures and filling defects. It is undoubtedly useful for the management of complex stone disease. We initially restricted our use of POC to the most challenging patients whom had previously undergone multiple ERCP's. We intend to evaluate POC further as a primary ERCP technique in patients with proximal biliary strictures.